GAMBARAN KARAKTERISTIK IBU DAN ANAK TERHADAP KEJADIAN GIZI KURANG PADA ANAK BALITA DI DESA SUKAWATI GIANYAR TAHUN 2014 - Parivindaraj Sundaraj (Intisari Sains Medis, 2015)
Background: Malnutrition is one of the leading health problems among Indonesians. The incidence of malnutrition and poor nutrition increases each year, especially in the province UPT Kesmas Sukawati I.Â Aim: This study aims to identify risk factors involved in the incidence of malnutrition in children under 5 years old in Sukawati Village, Gianyar.Method of Study: Study was conducted between November â€“ December 2014 using descriptive cross sectional study method. Subject of study are children under 5 years old in Sukawati Village, Gianyar consisting of 50 samples. Data was obtained through direct anthropometry measurements of children under 5and interview of mothers with toddlers through questionnaire. Data analysis was done descriptively and presented in tables and narrative.Result: Malnutrition according to weight/age in children under 5 years in Sukawati Village is 12%. 96% of children under 5 years with normal birth weight, 62% of children under 5 years without Exclusive breastfeeding, 30% of children under 5 years with poor diet intake, 26% of children below 5 years with low educated mothers, 64% of children below 5 years with working mothers, 48% of children below 5 years with low income families, and 52% of children below 5 years with mothers lacking knowledge in nutrition.Conclusion: Risk factors in children under 5 years with malnourished state are due to absence of exclusive breastfeeding for 6 months, poor diet intake, low educated mothers, working mothers, and mothers lacking knowledge in nutrition.